Prolactin does not affect human platelet aggregation or secretion - Reuwer, Anne Q.; Nieuwland, Rienk; Fernandez, Isabelle; Goffin, Vincent; van Tiel, Claudia M.; Schaap, Marianne C. L.; Berckmans, René J.; Kastelein, John J. P.; Twickler, Marcel Th. B. (Thrombosis and Haemostasis, 2009)
Platelets play an important role in the development of plaque formation and in the events after rupture of the atherosclerotic plaque, leading to atherothrombosis. Multiple hormones, either in excess or when deficient, are involved in the development of atherothrombotic disease, but, to which extent such hormones affect platelet function, is still controversial. It was the objective of this study to assess the ability of the pituitary hormone prolactin to affect platelet functions. Venous blood was collected from six healthy males. Platelet activation was studied by (i) flow cytometry in whole blood (exposure of P-selectin as a measure of platelet secretion, and binding of PAC-1 as a measure of ligand-binding conformation of αIIbβ3), and by (ii) optical aggregation and whole blood aggregation. All studies were performed without and with exposure to several concentrations of ADP (0.1, 0.5 and 1.0 μM) and prolactin (50 and 1,000 μg/l). The presence of the prolactin receptor was investigated by Western blot and flow cytometry. In response to either 50 or 1,000 μg/l prolactin, no evidence of platelet activation or aggregation was found. In addition, ADP-induced platelet activation or aggregation was not enhanced by prolactin. Finally, prolactin receptors could not be detected on the surface of platelets. The present data indicate that prolactin does not directly modulate platelet function.
Keywords: Atherothrombosis; prolactin; platelet activation; platelet aggregation; prolactin receptor